P136 Non-invasive assessment of diaphragm contractility using surface mechanomyography in healthy subjects - Lozano-García, M; Sarlabous, L; Moxham, J; Rafferty, GF; Jané, R; Jolley, CJ (Thorax, 2017)
IntroductionThe current gold standard assessment of diaphragm contractility involves invasive measures of transdiaphragmatic pressure (Pdi) (ATS/ERS 2002). Surface mechanomyography (sMMG) is a non-invasive measure of muscle fibre vibration during contraction. Sarlabous et al (ERJ 2015) reported a high correlation between diaphragm sMMG (sMMGdi) amplitude and inspiratory mouth pressure, a measure of global respiratory muscle function. To further validate the technique, the relationship between sMMGdi and Pdi was examined in this study, hypothesising that there would be a close relationship between sMMGdi and Pdi in healthy subjects.MethodsPdi and sMMGdi (right lateral chest) were measured in 12 healthy subjects (6 male, age 33 (30–38) years, BMI 22.2 (20.6–24.2) kg/m2) during an increasing inspiratory threshold loading protocol. sMMGdi signals were analysed using fixed sample entropy (fSampEn). Mean and peak values, and the area under the curve of inspiratory Pdi and fSampEn sMMGdi, were calculated and compared.ResultsStrong correlations between the non-invasive sMMGdi and the invasive Pdi measures were observed for all three parameters (figure 1).Abstract P136 Figure 1Relationship between the area under the curve (A), the mean value (B), and the peak value, and (C) of Pdi and fSampEn sMMGdi, during an increasing inspiratory threshold loading protocol. In each subfigure, the mean and standard deviation values of all healthy subjects are shown at rest and at 12%, 24%, 36%, 48%, and 60% of maximum mouth inspiratory pressure. In subfigure A, the entropy-time product (ETP) arid the pressure-time product (PTP) represent the area under the fSampEn sMMGdi and Pdi curves, respectively, multiplied by the respiratory rate.ConclusionThe strong correlation between measures of sMMGdi and Pdi in healthy subjects suggests that sMMGdi could provide a clinically applicable noninvasive index of respiratory muscle contractility in patients with respiratory muscle weakness for diagnosis and monitoring.